Technical and vocational education and training in Tajikistan and other countries in Central Asia key findings and policy options. - Izawa, Eiko Kanzaki; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
This publication details how technical and vocational education and training (TVET) has evolved in Tajikistan and other countries in Central Asia. It offers recommendations to enhance regional cooperation in labor market and TVET development.Tajikistan and other countries in Central Asia, such as Kazakhstan, the Kyrgyz Republic, Turkmenistan, and Uzbekistan, are striving to align TVET with their economic realities. Job shortage and the gap between TVET and the needs of employers must be addressed by these countries. The publication recommends improvements across different areas, including management and governance as well as regional collaboration and experience sharing.
Keywords: Technical,Vocational education -- Central Asia; Central Asia -- Economic integration; Electronic book